Dialectics of Da'wah, Politics, and Media in Madura (Analysis of RadarMadura.id News Discourse on Gus Miftah Distributing Money in Pamekasan) - Mariyam, Siti; Triyaningsih, Heny (UIN Fatmawati Sukarno Bengkulu, 2024)
This article examines the complex relationship between da'wah and politics in Madura, especially in the context of the politicized phenomenon of da'wah. The main focus is on discourse analysis of the RadarMadura.id news regarding the controversy over Gus Miftah distributing money in Pamekasan: how the media constructs the story through word choice and grammar to build a narrative related to this issue. This research is a qualitative study that uses discourse analysis as part of the interpretive method. The object of this research is news on RadarMadura.id with the title